The Solar Engine and Its Influence on Terrestrial Atmosphere and Climate 1994
DOI: 10.1007/978-3-642-79257-1_14
|View full text |Cite
|
Sign up to set email alerts
|

10Be as an indicator of solar variability and climate

Abstract: The atmospheric production rate of the cosmogenic isotope 10Be is modulated by the solar wind. Spectral analysis of a 560 year long 10Be concentration record from a Greenland ice core shows that this modulation process was active at all times even during quiet sun periods (Maunder minimum). To separate production effects from the effects of transport and deposition processes, three 10Be records of different length and time resolution were used to calculate the expected 14C variations.Comparisons with measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…For the Holocene a generally good correlation of 10 Be concentration in polar ice and ⌬ 14 C is found (Beer, 1994;Finckel and Nishiizumi, 1997). We are interested primarily in the 10 Be concentration of the atmosphere, which is related to the 10 Be concentration in ice through depositional processes (Finckel and Nishiizumi, 1997).…”
Section: ⌬ 14 C Changesmentioning
confidence: 92%
“…For the Holocene a generally good correlation of 10 Be concentration in polar ice and ⌬ 14 C is found (Beer, 1994;Finckel and Nishiizumi, 1997). We are interested primarily in the 10 Be concentration of the atmosphere, which is related to the 10 Be concentration in ice through depositional processes (Finckel and Nishiizumi, 1997).…”
Section: ⌬ 14 C Changesmentioning
confidence: 92%
“…Earth-satellite measurements in the last two decades have revealed that the total energy reaching the Earth varies by at least 0.1% over the 10-to 11-year solar cycle (12). Evidence of larger and longer term variations in solar output can be deduced from geophysical data (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Primary production of meteoric 10 Be is controlled by solar activity and magnetic field intensity [ Masarik and Beer , 2009], both of which vary over time [ Beer , 1994; Frank et al , 1997]. The subsequent distribution of primary meteoric 10 Be is controlled by atmospheric circulation, with annual precipitation being a strong predictor of total meteoric 10 Be fallout at any one location [ Heikkilä et al , 2009].…”
Section: Behavior Of Meteoric 10bementioning
confidence: 99%